2023
DOI: 10.3389/fonc.2023.1110881
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of endoplasmic reticulum stress in the cellular plasticity of cancer cells

Abstract: Cellular plasticity is a well-known dynamic feature of tumor cells that endows tumors with heterogeneity and therapeutic resistance and alters their invasion–metastasis progression, stemness, and drug sensitivity, thereby posing a major challenge to cancer therapy. It is becoming increasingly clear that endoplasmic reticulum (ER) stress is a hallmark of cancer. The dysregulated expression of ER stress sensors and the activation of downstream signaling pathways play a role in the regulation of tumor progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 164 publications
0
3
0
Order By: Relevance
“…In some infections, pathogens or immune responses can lead to the upregulation and release of vimentin into the extracellular space 28,40,42–45 . Various forms of cellular stress, such as oxidative or endoplasmic reticulum (ER) stress, have also been associated with vimentin upregulation, potentially increasing its extracellular pool during cell activation or injuries 46,47 …”
Section: Extracellular Vimentin—in the Shadow Of Its Filamentous Siblingmentioning
confidence: 99%
“…In some infections, pathogens or immune responses can lead to the upregulation and release of vimentin into the extracellular space 28,40,42–45 . Various forms of cellular stress, such as oxidative or endoplasmic reticulum (ER) stress, have also been associated with vimentin upregulation, potentially increasing its extracellular pool during cell activation or injuries 46,47 …”
Section: Extracellular Vimentin—in the Shadow Of Its Filamentous Siblingmentioning
confidence: 99%
“…Moderate ER stress induction is correlated to the activation of the pro-survival genes that regulates amino acid metabolism, ER chaperones, redox reaction, protein folding, and autophagy [ 361 ]. In some cases..of cancer like in HCC, it has been found that endoplasmic reticulum stress-mediated activation of autophagy also plays a role in upregulating MRP1 that enhances intracellular drug or toxic heavy metal efflux thus protecting cells from apoptosis [ 362 , 363 ]. Autophagy is shown to influence some crucial drug-resistant enzymes (detoxifying enzymes) like aldehyde dehydrogenase (ALD1A3) and thus arbitrate in acquired drug resistance in temozolomide-treated human glioblastoma cells [ 141 ].…”
Section: Autophagy and Er Stress (Upr) Are Utilized By Cancer Cells T...mentioning
confidence: 99%
“…Activation of cellular adaptation mechanisms, such as the UPR, against ER stress is known to promote the plasticity of cancer cells, thus dynamically regulating the metastasis, recurrence, evasion of antitumor immunity, and chemoresistance of tumors [ 13 , 14 ]. ER stress and the UPR are tightly regulated by three ER transmembrane proteins, the inositol-requiring enzyme 1 (IRE1), protein kinase R-like ER kinase (PERK), and activating transcription factor 6 (ATF6), which are UPR sensor proteins [ 15 ].…”
Section: Introductionmentioning
confidence: 99%